Implementasi Kebijakan Penetapan Upah Minimum di Kota Semarang - Muhammad Farrel Radiand Mirza; R. Slamet Sanstoso; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Covid-19 Pandemic that hit Indonesia, especially Semarang, contributes significant impact on business operation and workforce. The social restriction policy imposed by the city government affects business operation. Many business suffer losses or even close permanently which affecting massive layoffs. The determination of minimum wage which coincidence with Covid19 Pandemic leads the government to intervene the minimum wage rate. The government intervention in setting the minimum wage is needed. Government needs to ensure that the minimum wage setting accommodates the sustainability of business world and the other hand accommodates the welfare of workers during pandemic. This study aimed to determine the implementation of minimum wage Policy in Semarang during Covid-19 Pandemic. This study used a qualitative descriptive method. The data in this study were collected by interview, observation, and literature review. The results of this study showed that the implementation of minimum wage policy in Semarang had been consistent with Government Ordinance No. 78/2015 and also had been accommodate all interests so all policy target parties agree with the minimum wage rate in Semarang.